Images of childhood - Wyver, Shirley R.; Whiteman, Peter; Children and Childhoods Symposium (2010 : Macquarie University, N.S.W.) (Newcastle upon Tyne, UK : Cambridge Scholars, 2012)
Decisions relating to children's lives, including formation of policies about children and young people, advocating for children's rights, educational instruction and parenting, all depend on images of children and childhoods. Nonetheless, prevailing images of childhood are not often subject to critique. Images of Childhood offers an examination of public images of childhood in the context of research findings. Authors from a wide range of disciplines, including early childhood, psychology, ...
TABLE OF CONTENTS; INTRODUCTION; CHAPTER ONE; PART I; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; PART II; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; PART III; CHAPTER EIGHT; CHAPTER NINE; CHAPTER TEN; CONCLUSION; CHAPTER ELEVEN; CONTRIBUTORS
Contributions by Angela Crettenden, Kathy Cologon, Fred Ebbeck, Marjory Ebbeck, Robyne Garrett, Helen Little, Halla Malik, Andrew McGrath, Toan Nguyen, Berenice Nyland, Timothy Olds, Parimala Raghavendra, Kirrilly Thompson, Shiela Warrier, Peter Whiteman, Shirley Wyver.
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: Children; Infants -- Development; Early childhood education -- Australia -- Congresses; Early childhood education -- Activity programs -- Congresses; Early childhood education -- Congresses; Nourrissons -- Développement.; Éducation de la première enfance -- Australie -- Congrès.; Éducation de la première enfance -- Méthodes actives -- Congrès.; Éducation de la première enfance -- Congrès.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Children; Early childhood education; Early childhood education -- Activity programs; Infants -- Development; Australia; Conference papers and proceedings